IDRC 2006 IDRC, Peter Bennett. - International Development Research Center (Ottawa, Canada International Development Research Center, 2006)
Canada's International Development Research Center (IDRC) is one of the world's leading insttitutions in the generation and application of new knowledge to meet the challanges of international development. For 35 years, IDRC has worked in close collaboration with researchers from the developing world as theys strive to build healtheir, more equitable, and more properous societies.
The development dossiers present special thematic collections on selected IDRC activities. Each tackles a current and pressing issue in sustainable development, organizing and distilling IDRC's research experience with an eye to drawing out important lessons, observations and recommendations for decision-makers and policy analysts.
IDRC Books publishes research results and scholarly studies on global and regional issues related to sustainable and equitable development. As a specialist in development literature, IDRC Books contributes to the body of knowledge on these issues to further the cause of global understanding and equity.
Disc. 1 Contents: IDRC 2006: Annual report ; News and features ; How to apply for Funding ; Development Dossier ; Catalogue of publications.
Disc. 2 Contents: Bookcase 2006: 101 full-text e-books
IDRC encourages the use of the material on this CD product for academic, educational, and research purposes. We are eager to learn how the information on this CD is being used and will generally grant permission for reproduction or redistribution for nonprofit purposes, provided suitable credit and and reference is given to IDRC and the original source material. For permission to reproduce or redistribute this CD or any portion thereof.
Donated by Rodelio Subade (2006)
Keywords: Economics; Environment and Biodiversity; Food and Agriculture; Health; Information & Communication; Natural Resources; Science and Technology; Socail and Political Sciences